UNSUSTAINABLE YOUTH EMPLOYMENT IN THE DIGITAL ECONOMY: COGNITIVE DISSONANCE AND SOCIAL MECHANISMS OF ADAPTATION - Oksana V. Leshkova; Maria V. Shimolina (Russian Studies in Culture and Society, 2025)
The article examines the phenomenon of cognitive dissonance among young people employed in the digital economy, amid the growth of precarious employment in Russia. According to the Federal Tax Service and Rosstat, from 2020 to 2024, the number of self-employed people exceeded 12 million people, while young people actively choose platform employment, despite the awareness of its risks. The author analyzes this paradox through the prism of theories of cognitive dissonance (L. Festinger), risk society (U. Beck) and the precariat (G. Standing), revealing the contradiction between the rhetoric of "freedom" and real instability.